Rural To Urban Migration Among Agricultural Households In Indonesia: Evidence From The 2015 Intercensal Population Survey (SUPAS) - Sitompul, Thomson (JALOW | Journal of Agribusiness and Local Wisdom, 2026)
This study analyzes rural–urban migration and non-permanent mobility in Indonesia using secondary data from the Statistics Indonesia 2015 Intercensal Population Survey (SUPAS 2015). Grounded in the Harris–Todaro framework and contemporary migration theories, the research examines the socioeconomic determinants of migration decisions and the growing relevance of commuter and seasonal mobility patterns. Rural–urban migration is conceptualized as a rational decision based on expected income differentials, employment opportunities, and access to urban facilities, while recognizing structural imbalances in the labor market that may generate urban unemployment and informal sector expansion. This study employs a quantitative and qualitative research design supported by a systematic literature review. The literature review was conducted to identify theoretical frameworks, empirical findings, and methodological approaches related to rural–urban migration. Previous scholarly articles were carefully examined to construct the conceptual framework and to determine relevant variables for empirical analysis. Urbanization in Indonesia demonstrates both positive and negative implications. On the one hand, agglomeration economies enhance productivity, income, and access to education and health services. On the other hand, rapid urban growth contributes to congestion costs, informal employment, environmental degradation, and urban poverty. The study concludes that migration and non-permanent mobility are integral components of Indonesia’s demographic and economic transformation, requiring balanced regional development policies and improved urban governance to maximize benefits while minimizing social and economic costs.